The syntax of early English (Cambridge University Press, 2000)
This book is a guide to the development of English syntax between the Old and Modern periods. Beginning with an overview of the main features of early English syntax, it gives a unified account of the significant grammatical changes that occurred during this period. Four leading experts demonstrate how these changes can be explained in terms of grammatical theory and the theory of language acquisition. Drawing on a wealth of empirical data, the book covers a wide range of topics including changes in word order, infinitival constructions and grammaticalization processes